Welcome to Westonci.ca, where curiosity meets expertise. Ask any question and receive fast, accurate answers from our knowledgeable community. Join our platform to connect with experts ready to provide accurate answers to your questions in various fields. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
Given function in the question is,
[tex]f(x)=2-5x-x^2[/tex]
To find the difference coefficient for the given function, we use the expression as [tex]\frac{f(3+h)-f(3)}{h}[/tex].
[tex]f(3+h)=2-5(3+h)-(3+h)^2[/tex]
[tex]=2-15-5h-(9+h^2+6h)[/tex]
[tex]=(2-15-9)-(5h+6h)-h^2[/tex]
[tex]=-22-11h-h^2[/tex]
[tex]=-(22+11h+h^2)[/tex]
[tex]f(3)=2-5(3)-(3^2)[/tex]
[tex]=2-15-9[/tex]
[tex]=-22[/tex]
Now substitute these values in the expression for the difference coefficient,
[tex]\frac{f(3+h)-f(3)}{h}=\frac{-(22+11h+h^2)-(-22)}{h}[/tex]
[tex]=\frac{-22-11h-h^2+22}{h}[/tex]
[tex]=\frac{-11h-h^2}{h}[/tex]
[tex]=-(11+h)[/tex]
Therefore, Value of the difference quotient for the given function is[tex]-(11+h)[/tex].
Learn more,
https://brainly.com/question/11535593
Thank you for visiting our platform. We hope you found the answers you were looking for. Come back anytime you need more information. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.